SYNCHRONIZATION IN RELATIVITY IN THE CONTEXT OF THE TWIN PARADOX - Iyer, Chandru (International Journal of Research -GRANTHAALAYAH, 2018)
convention adopted by SRT in the context of the Twin Paradox; we place two spatially separated observers in the stationary and travelling frames and discuss the synchronization issues at the completion of the travels.